Status of C-Reactive Protein, Cellular and Clinical Parameters in Neonates with Risk of Sepsis in Tertiary Center of Mid-Western Nepal - Sapkota, Suraksha; Danai, Anu; Malla, Pragya; Sah, Bishesh (Journal of Nepalgunj Medical College, 2025)
Introduction: Neonatal sepsis refers to a bloodstream infection which impacts infants under 28 days of age. Symptoms may encompass irregular vital signs and respiratory discomfort. C-reactive protein served as a vital diagnostic marker; nevertheless, its low sensitivity in early identification necessitates periodic assessments for accurate diagnosis and therapy monitoring. Aims: This study assessed C-reactive protein levels, cellular parameters, and clinical indicators in neonates predisposed to sepsis at a tertiary care facility. Methods: Hospital based prospective study, conducted on 150 neonates in paediatrics and biochemistry department of Nepalgunj Medical College from June 2024 to October 2024. C-reactive protein, whole blood count, platelets count, Immature/ total neutrophil ratio were calculated along with the clinical findings suggesting sepsis were recorded. Major neonatal anomalies and prior antibiotic use led to exclusion. Results: Among 150 at-risk neonates, 65.3% were male, 46% were preterm and 45.3% had low birth weight. Elevated C-reactive protein (>6 mg/L) was found in 84.7%, with 68% showing tachypnea and 53.3% delayed capillary refill. Temperature variability (90%) and tachycardia (70%) were common. Laboratory findings showed high C-reactive protein (mean 16.8 mg/L), neutrophil predominance (61%), and raised Immature to total neutrophil ratio (0.25). Late-onset cases had more severe clinical and inflammatory profiles than early-onset cases. Conclusion: C-reactive protein, as a biochemical marker, was observed in the majority of neonates at risk of sepsis, while temperature variability, tachycardia and reduced urine output were common clinical features indicating systemic compromise.